2013
DOI: 10.1111/cch.12056
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring the psychosocial value of weekend camping experiences for children and adolescents with complex heart defects

Abstract: This qualitative study showed that children living with complex CHD valued the opportunity for participating in weekend camping experiences in the company of peers with similar heart defects. Findings contribute to a better understanding of what programme features and processes were considered meaningful. Given the scarcity of resources to devote to such social support activities, the findings may help professionals to plan effective interventions to maximize benefits during a shorter camping experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(69 citation statements)
references
References 23 publications
3
66
0
Order By: Relevance
“…To make interventions available to those who need them, service providers should ensure they have adequate funding for equipment (e.g., Nicholas et al, ), staff expertise in intervention design and delivery (Whittemore, Grey, Lindemann, Ambrosino, & Jaser, ), and space to stage an intervention ( et al, ). Health and social care staff play a key role in recognizing the mental health needs of CYP and supporting them and their families to access an intervention that is appropriate for their needs (e.g., Desai, Sutton, Staley, & Hannon, ;Fair, Connor, Albright, Wise, & Jones, ;Lewis et al, ). As discussed within A Therapeutic Foundation below, CYP find it validating when their emotions and experiences are recognized by others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To make interventions available to those who need them, service providers should ensure they have adequate funding for equipment (e.g., Nicholas et al, ), staff expertise in intervention design and delivery (Whittemore, Grey, Lindemann, Ambrosino, & Jaser, ), and space to stage an intervention ( et al, ). Health and social care staff play a key role in recognizing the mental health needs of CYP and supporting them and their families to access an intervention that is appropriate for their needs (e.g., Desai, Sutton, Staley, & Hannon, ;Fair, Connor, Albright, Wise, & Jones, ;Lewis et al, ). As discussed within A Therapeutic Foundation below, CYP find it validating when their emotions and experiences are recognized by others.…”
Section: Resultsmentioning
confidence: 99%
“…Parents highlighted the importance of flexibility in the delivery of interventions, such as considering the time of day (e.g., Brodeur, ) and setting (e.g., Muskat et al, ). Providing opportunities for CYP to maintain the peer relationships formed during an intervention via social media (e.g., Kirk & Milnes, ) or organized events (e.g., Desai et al, ; Lewis et al, ) may help maintain the beneficial effects of the social support received through an intervention (as discussed within the construct Social Support) beyond its scheduled endpoint.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that the participants in everyday life had felt stigmatised by others, but meeting other young people with the same chronic disease had made them feel less deviating and improved their sense of experiencing normality (Desai et al . ). Our participants experienced greater acceptance of themselves and this had been particularly important for everyday life.…”
Section: Discussionmentioning
confidence: 97%
“…Two studies have also shown that peer support amongst young people with chronic disease contributed to a sense of normality (Desai et al . ; Tong et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation